Cultivation of Students' Spiritual Awareness Through the Integration of PAI Learning and Extra-Curricular Activities at Senior High School (SMAN) 2 Teluk Kuantan, Kuantan Singingi - Alhairi, Alhairi; Akbar, Helbi; Lasmiadi, Lasmiadi; Andrizal, Andrizal (JASNA : Journal For Aswaja Studies, 2024)
The spiritual building is an effort to carry out mental or spiritual refreshment in the form of belief, faith, ideology, ethics, guidelines and guidance. Spiritual development can be done using various media, one of which comes from religion, which is called "religious spiritualism." Religious communities must develop, strengthen or rebuild the spiritual role of religion. SMAN 2 Teluk Kuantan always instills spiritual values in its students, both through education, teaching and other activities such as the weekly wirid, which is held every Friday to spiritual tausiah activities on Islamic holidays where all of this is carried out in order to internalize the spirit of faith and student self-confidence. The aim of the author in conducting this research is to find out the extent of religious spiritual awareness, especially among students at SMAN 2 Teluk Kuantan who have embraced Islam since birth, which was inherited from their parents and what factors influence religious spirituality to increase and decrease in them. Based on observations, some students ignore their obligations as Muslims, such as praying five times a day, Friday prayers, reading the Koran and lacking feelings of guilt when committing mistakes that are prohibited by religion (Islam), such as gambling, consuming alcohol and other immoralities. Even though they have been given education related to this, especially in PAI-BP subjects, which are mandatory curriculum subjects. As the author explains in the background of the problem, the focus discussion in this research is related to an analysis study of the level of religious spiritual awareness of students at SMAN 2 Teluk Kuantan. With a problem formulation: What is the level of spiritual and religious awareness of students at SMAN 2 Teluk Kuantan, and what are the factors that influence it? The population in this study were all students of SMAN 2 Teluk Kuantan.Â